Identifcation and fine mapping of qHSW1, a major QTL for hundred-seed weight in mungbean - Han, Xuesong; Zhao, Long; Yu, Juan; Wang, Xingmin; Zhang, Shilong; Li, Li; Liu, Changyan (Frontiers in Plant Science, 2025)
Mung bean, an important economic crop, is considered a crop with relatively high levels of plant protein constituents and is consumed as both a vegetable and a grain. Among various yield-related traits, hundred-seed weight (HSW) is crucial in determining mung bean production. This study employed a recombinant inbred line (RIL) population of 200 lines that were genotyped via whole-genome resequencing to exploit genetic potential in the identification of HSW-associated quantitative trait loci (QTLs) across four environments. We identified 5 QTLs for HSW, each explaining 2.46–26.15% of the phenotypic variance. Among these, qHSW1 was mapped on chromosome 1 in all four environments, explaining 16.65-26.15% of the phenotypic variation. Fine mapping and map-based cloning procedures, along with progeny testing of recombinants, aided in narrowing the candidate interval for qHSW1 to 506 kb. This identification of the qHSW1 genomic interval and closely linked markers to qHSW1 could prove valuable in breeding efforts for improved mung bean cultivars with higher seed weight.